2015
DOI: 10.1002/ceas.12009
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness‐Based Awareness and Compassion: Predictors of Counselor Empathy and Anxiety

Abstract: Mindfulness-based awareness and compassion were examined as predictors of empathy and anxiety among 152 master's-level counseling interns. Results of hierarchical multiple regression analysis supported that awareness and compassion differentially contributed to explaining the variance in counselor empathy and anxiety. Implications for counselor education are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 37 publications
(58 reference statements)
4
55
0
2
Order By: Relevance
“…In the original IRI, respondents endorse responses on a 5‐point Likert‐type scale, ranging from A ( does not describe me well ) to E ( describes me very well ). The results of prior research have demonstrated adequate reliability evidence for the PT (α = .75) and EC (α = .79) subscales in samples of CITs (C. L. Fulton & Cashwell, ). In the current study, Cronbach's alphas for the PT and EC subscales indicated adequate reliability (see Table ).…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…In the original IRI, respondents endorse responses on a 5‐point Likert‐type scale, ranging from A ( does not describe me well ) to E ( describes me very well ). The results of prior research have demonstrated adequate reliability evidence for the PT (α = .75) and EC (α = .79) subscales in samples of CITs (C. L. Fulton & Cashwell, ). In the current study, Cronbach's alphas for the PT and EC subscales indicated adequate reliability (see Table ).…”
Section: Methodsmentioning
confidence: 92%
“…Items for the original FFMQ asked participants to indicate the extent to which statements are true for them by selecting responses on a Likert‐type scale ranging from 1 ( never or very rarely true ) to 5 ( very often or always true ). The FFMQ has demonstrated reliability evidence in samples of CITs (C. L. Fulton & Cashwell, ; Ivers, Johnson, Clarke, Newsome, & Berry, ). The FFMQ‐SF has demonstrated reliability evidence among adults with mild depression or anxiety from the Netherlands (Bohlmeijer et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research from neuroscience and psychotherapy keeps confirming positive outcomes associated with meditation techniques for improving health care, including mental health, brain functions, and emotional regulation (Fulton & Cashwell, 2015;Marshall, Laures-Gore, & Love, 2018). The positive effects of Eastern meditation are supported by Western scientific research.…”
Section: Osho As Eastern Meditation In a Western Context Many Meditamentioning
confidence: 92%
“…These practices are being utilized to both strengthen direct practice clinical skills (Gockel, 2015) and to reduce burnout among social work and counseling students and interns (Gockel, Burton, James & Bryer, 2013;Testa & Sangganjanavanich, 2016). Fulton and Cashwell (2015) observed a positive relationship between mindfulness, compassion and counselor empathy for master's level counselor interns. With regards to burnout Decker and colleagues found that mindfulness reduced compassion fatigue and increased compassion satisfaction among MSW students (Decker, Brown, Ong, & Stiney-Ziskind, 2015), and Bonifas and Napoli (2014) found that mindfulness improved quality of life ratings for MSW students despite levels of stress persisting.…”
Section: Social Work and Counselor Educationmentioning
confidence: 99%